The Garden of Knowledge and Virtue alumni memories and reflections - Othman, Azam (IIUM PRESS, 2014)
It features the reflections of various IIUM alumni on their journeys as students of the IIUM and their lives after graduation. These journeys are described and shared in 18 chapters of the book, detailing the colourful experiences and perspectives of IIUM alumni from all the different kulliyyahs and centres of the University.